Analysis of The Influence of Brand Awareness and Customer Satisfaction on Corporate Image and Its Impact on Customer Loyalty on Laurier Products PT. Kao Indonesia (Bina Nusantara University, 2022)
This study aims to look at the effect of brand awareness and customer satisfaction to the corporate image and its impact on customer loyalty in product laurier PT Kao Indonesia. Customer Loyalty is one of the core objectives are pursued in modern marketing. This is due to the loyalty of the company will get profibilitas expected in the long term. This study uses a quantitative approach and involves 52 respondents in villages Cikoko as samples collected by using probability sampling and simple random sampling. Processing data using SPSS 24 and the results of this study showed that brand awareness, customer satisfaction and corporate image have a significant effect on customer loyalty.